Makna Ritual methik di Kalangan Petani: Studi Tentang Kearifan Lokal Petani Desa Sumbersewu Kabupaten Banyuwangi (The Ritual Meaning of methik in Farmer Sphere: A Study on Farmer Local Wisdom in Sumberwaru Village, Banyuwangi Regency) - Wijaya, Rizky Romy; Jannah, Raudlatul (University of Jember, 2019)
AbstractMost of the farmers in Sumbersewu Village of Banyuwangi Regency are Muslim and Hindu. The local people still uphold the Javanese culture that has been passed down by their ancestors. One of them is the methik ritual. The methik ritual ceremony is a process done at the time of harvesting agricultural produce. The procession of methik ritual have several stages such as determining the good day, preparing the offerings, afterwards to the place of execution that can be at the rice field or at home, after that begins with the reading of prayers or mantras performed by elders or shaman and ends with eating together. In the methik ritual, there are three meanings that are generated and to this day are still maintained by the local community, especially the first peasants, as an expression of gratitude to the creator or Sang Hyang Widhi in the belief of Hindus and Allah SWT in the belief of Muslims Have been given good fortune and safety. Second, the protection where the methik ritual in this case is done to ask the salvation to the creator to avoid the calamity associated with farming. Thirdly, as a preservation where in this case the methik ritual is one of the ancestral cultural heritage whose existence must remain in guard and preserved. Local wisdom to the farmers of Sumbersewu Village is a form of reflection of harmony with nature.Keywords: local wisdom, meaning of methik, farmer, and nature.